Pengaruh Cyber Public Relations Pada Event Festival Jajanan Bango 2022 Terhadap Brand Image Bango : Survei Pada Pengikut Akun Instagram @bangowarisankuliner - Fathur Rodzi Firmanto; Winda Dwi Astuti Zebua (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In this era of globalization, rapid development of information technology and digitalization, the role of Cyber Public Relations in influencing brand image has become crucial to the success of companies. In this context, "Bango," a well-known seasoning brand among Indonesians, has utilized Cyber Public Relations strategies to promote and publicize the Bango Jajanan Festival Event. The approach taken in this research is to use a quantitative approach to measure the influence of cyber public relations on Instagram on Bango's brand image. Using a quantitative approach, it is necessary to conduct a survey research method. Based on the results of research and data analysis, it can be seen that this study uses two variables consisting of independent variables (X), namely Cyber Public Relations in publicizing the 2022 Bango Snack Festival Event on the dependent variable (Y), namely Bango Brand Image. From the results of this study, the t_hitung value is 12.378 > 2.628 t_table, so H_o is rejected and H_a. So that the results show that there is a significant influence between the influence of Cyber Public Relations on Brand Image. In addition, based on the correlation value R, it shows that the influence of Cyber Public Relations (X) in publicizing the 2022 Bango Snack Festival Event on Bango's Brand Image (Y) has a positive, strong, and high effect by obtaining an R value of 0.681. While the R_Square number is 0.463. The R_square number is also known as the coefficient of determination, the amount of determination is 0.463 or equal to 46.3%, this figure means that 46.3% of Cyber Public Relations in publicizing the 2022 Bango Snack Festival Event affects Bango's Brand Image. While the remaining 53.7% is influenced by other variables not mentioned in this study.